PENDATAAN JUMLAH NASABAH BRI YANG IKUT SERTA DALAM ASURANSI ANAK PERUSAHAAN BRI DAN JUMLAH NASABAH BRI YANG TIDAK IKUT SERTA DALAM ASURANSI BRI DI KANCA MUARA BULIAN : Strategy, Marketing, BRILife Syariah - Nurjani, Yeni; Inda Aditya, Meydi (LP2M Universitas Nurdin Hamzah, 2023)
BRILife Syariah Muara Bulian branch is one of the companies engaged in insurance. In an effort to increase its sales, the insurance policy in Muara Bulian City generally uses several marketing strategies. This type of research is descriptive with a qualitative approach. Data collection used using interviews, documentation studies and observations. The study in this study is to find out “Agent Marketing Strategies in Maintaining Customer Loyalty at PT.BRILife Syariah Muara Bulian branch with aspects of the research are: about insurance products, Premium Prices, Promotions, Places, People and Physical Facilities.The results show that the Branch of PT.BRILife Syariah Muara Bulian.